Clinical outcome of patients with carcinoma ex pleomorphic adenoma of the parotid gland: A comparative study from a single tertiary center. Issue 4 (10th April 2014) - Lim, Chwee Ming; Hobson, Candace; Kim, Seungwon; Johnson, Jonas T.
Abstract: Background: Carcinoma ex pleomorphic adenoma (CXPA) of the parotid gland is a high‐grade cancer and the prognosis of this cancer has not been compared with non‐CXPA high‐grade primary parotid cancer. Methods: Retrospective medical chart review of patients with surgically treated high‐grade primary parotid cancer (21 CXPA and 52 non‐CXPA) was performed with correlation with disease‐specific survival, locoregional recurrence, and distant recurrence. Results: Despite having similar stage of cancer and extent of surgical resection, patients with CXPA had a lower disease‐specific survival compared to non‐CXPA high‐grade primary parotid cancer ( p = .02). Salivary duct cancer (SDC) was the commonest histologic variant in both cohorts and around 40% of patients with SDC died of distant recurrence that occurred within 3 years from diagnosis. Conclusion: CXPA of the parotid gland is a more aggressive cancer compared to non‐CXPA high‐grade primary parotid cancer. SDC was associated with a high chance of delayed distant recurrence, which contributed directly to the mortality of this cancer. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 543–547, 2015